2011
DOI: 10.5194/nhess-11-3097-2011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Arias Intensity of historical earthquakes using modified Mercalli intensities and artificial neural networks

Abstract: Abstract. This paper presents the development of a nonparametric forecast model based on artificial neural networks for the direct assessment of Arias Intensity corresponding to a historic earthquake using seismic intensity data. The neural models allow complex and nonlinear behaviour to be tracked. Application of this methodology on earthquakes with known instrumental data from Greece, showed that the artificial neural network forecast model have excellent data synthesis capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…La Intensidad de Arias (IA) es una medida instrumental que sirve para determinar los daños que un terremoto provoca en las estructuras y edificaciones. El SMA-LIS muestra el cálculo de la IA para la componente norte-sur (NS) y este-oeste (EW) de los registros de aceleración que tuvieron valores superiores a los 2,0 cm/s2, así como el valor total de esta que corresponde a la sumatoria de componentes horizontales (Tselentis, 2011). La tabla 1 muestra los valores de la IA calculados para el mismo evento de la figura 7.…”
Section: Aceleración Y Velocidad Máximaunclassified
“…La Intensidad de Arias (IA) es una medida instrumental que sirve para determinar los daños que un terremoto provoca en las estructuras y edificaciones. El SMA-LIS muestra el cálculo de la IA para la componente norte-sur (NS) y este-oeste (EW) de los registros de aceleración que tuvieron valores superiores a los 2,0 cm/s2, así como el valor total de esta que corresponde a la sumatoria de componentes horizontales (Tselentis, 2011). La tabla 1 muestra los valores de la IA calculados para el mismo evento de la figura 7.…”
Section: Aceleración Y Velocidad Máximaunclassified
“…Suhadolc et al, 1988;Zahradnic, 1989;Sirovich, 1996) and compare it with observed data throughout a trial and error process. Recently, for non-linear modelling, neural networks and neuro-fuzzy modelling approaches have received a great deal of attention (Huang and Leung, 1999;Tselentis and Vladutu, 2010;Tselentis, 2011). Neuro-fuzzy modelling is concerned with the extraction of models from numerical data representing the behaviour of a system.…”
Section: G-a Tselentis and E Sokos: Relationship Between Isoseismalmentioning
confidence: 99%
“…Since the relation between isoseismal area and seismic magnitude is strongly nonlinear, artificial neural networks (ANN) are particularly suited for treating macroseismic data (Tung et al, 1994;Davenport, 2004;Tselentis 2011). An ANN is an information processing paradigm that is inspired by the way biological nervous systems, such as the brain, process information.…”
Section: Artificial Neural Network Approximationmentioning
confidence: 99%
See 1 more Smart Citation